Hedge funds and the financial crisis : evaluation of risk patterns - Tavares, Filipe Calixto (2016)
This dissertation aims to explore the impact of the financial crisis of 2007-08 on the equity holdings of U.S. hedge funds in terms of risk, analyzing its evolution from early 2000 until late 2015. I register the expected positive reaction of the equity portfolio risk of the U.S. hedge funds to the crisis. This is in part fueled by both the acquisition of risky stocks and the sale of safer ones. From the Fama-MacBeth regression I obtain several relations with respect to the equity portfolio volatility, in particular, that investing relatively more in growth stocks, diversifying more your portfolio, and having a relatively higher equity portfolio valuation lead, individually, to a reduction on risk, on average. On the other hand, investing relatively more in small cap stocks, most likely, increases volatility, on average. Finally, hedge funds that invest more in stocks with relatively lower capital expenditures are expected to score a higher level of volatility, on average, however, this relation reverses as the crisis hits and remains that way in the post-crisis period.